Professional burnout in nurses measured by the Maslach Burnout Inventory questionnaire in the scientific literature between 2008 and 2022 - Jaślan, Dorota; Różańska, Anna; Siewierski, Tomasz; Nowacka, Anna L. (Nursing Problems / Problemy Pielęgniarstwa, 2024)
In professions such as nursing, close, intensive contact with other people and high emotional involvement can cause the occurrence of professional burnout syndrome. The aim of the study was to investigate work-related burnout by analysing articles describing research on this issue among nurses published in medical journals (2008-2022). Data were obtained from a review (March-April 2023) of electronic databases: PubMed, Google Scholar, and EBSCO. By analysing selected articles, the work describes the research tools that are most often used to study occupational burnout (Maslach Burnout Inventory [MBI], Oldenburg Burnout Inventory [OLBI], Copenhagen Burnout Inventory [CBI]) and the broader purpose of the con-ducted research and the main risk factors related to professional burnout. The article describes the phenomenon of burnout, its causes, symptoms, consequences, and correlating phenomena. The results of occupational burnout research conducted with the use of MBI were presented. Despite the in-depth analysis of the research results of selected articles, it is impossible to clearly tell which of the symptoms of occupational burnout is dominant. The average burnout in 3 dimensions of the MBI ranges due to organisational and cultural differences in healthcare systems in various countries where nurse burnout was studied.